PENGARUH PENGETAHUAN MANAJEMEN BARBASIS SEKOLAH DAN KECERDASAN EMOSIONAL TERHADAP KEPEMIMPINAN KEPALA MADRASAH TSANAWIYAH KABUPATEN PATI - Ali Su'udi; Nurkolis Nurkolis; Akmal Akmal (Jurnal Manajemen Pendidikan (JMP), 2016)
The purposes of this research are: (1) to determine the influence of school-based management knowledge to the school leadership; (2) to determine the influence of emotional intelligence on school leadership; (3) to determine the influence of school-based knowledge management and emotional intelligence on school leadership. The populations in this research are all heads of private Religion Junior High School (MTs)  in KKMTs Margoyoso and Gembong Pati totaling 90 people, with a sample of 47 people by using simple random sampling technique. The data collection method used is a questionnaire. Analysis of the data uses descriptive analysis, test requirements and hypotheses test include simple linear regression analysis to determine the influence of knowledge-based management school to school leadership, and multiple regression analysis to determine the influence of knowledge of school-based management and emotional intelligence together against school leadership. Analyzing data used SPSS for Window Release 16.From the results of this research are that the average acquisition of school-based management knowledge score 113.61 including high category, the average acquisition emotional intelligence score was 106.31 including enough categories, and the average acquisition score 103,17 including school leadership category quite well. The test results of the research data obtained prerequisite normal distribution of data, homogeneous, linear, and not multicolinier. Hypothesis tests found: (1) There is a positive influence on the school-based management knowledge of school leadership that is expressed by the equation Ŷ=30,003+ 0,644X1; the strength of correlation of 0,780 with a contribution of 0,608 or 60,8%. (2) There is a positive influence of emotional intelligence on school leadership expressed by the equation Ŷ = 34.276+0,648X2; the strength of correlation of 0.957 with a contribution of 0.916 or 91.6%. (3) There is a positive influence of school-based knowledge management and emotional intelligence together against the leadership of the principal expressed by the equation Ŷ = 22.067+ 0, 310X1 + 0, 432X2; the strength of correlation of  0,864 with a contribution of 0,747 or 74,7%.